2015
DOI: 10.1016/j.scitotenv.2015.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination of home garden soils and cultivated vegetables in the province of Brescia, Italy: Implications for human exposure

Abstract: Background For the past century, ferroalloy industries in Brescia province, Italy produced particulate emissions enriched in manganese (Mn), lead (Pb), zinc (Zn), copper (Cu), cadmium (Cd), chromium (Cr), iron (Fe), aluminum (Al). This study assessed metal concentrations in soil and vegetables of regions with varying ferroalloy industrial activity levels. Methods Home gardens (n=63) were selected in three regions of varying ferroalloy plant activity duration in Brescia province. Total soil metal concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 49 publications
1
33
0
3
Order By: Relevance
“…The lack of observed correlations between soil and plant heavy metal concentration has also been observed in a number of other studies (Menzies et al, 2007;Ferri et al, 2015). The absence of correlations between soil cadmium and plant cadmium concentration and soil lead and plant lead concentration may be due to a number of factors already discussed, i.e.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The lack of observed correlations between soil and plant heavy metal concentration has also been observed in a number of other studies (Menzies et al, 2007;Ferri et al, 2015). The absence of correlations between soil cadmium and plant cadmium concentration and soil lead and plant lead concentration may be due to a number of factors already discussed, i.e.…”
Section: Discussionmentioning
confidence: 52%
“…In a study by Ferri et al (2015) it was observed that unwashed spinach leaves had a higher concentration of heavy metals compared to washed spinach leaves. This has also been observed in a number of other studies where thorough washing decreases the concentration of heavy metals in leaves (Caselles, 1997;Oliva and Valdés, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we draw attention to the role of contaminated soil in urban areas, which often contains dangerous levels of heavy metals (Cheng et al, 2011;Ferri et al, 2015). Heavy metals are present in the soil of many urban vegetable gardens in the United States and Europe (Clark et al, 2008;Cheng et al, 2011;Burt et al, 2014;Ferri, et al, 2015), prompting questions about the potential health consequences of UPA in contaminated areas.…”
Section: Urban Food Productionmentioning
confidence: 99%
“…Heavy metals are present in the soil of many urban vegetable gardens in the United States and Europe (Clark et al, 2008;Cheng et al, 2011;Burt et al, 2014;Ferri, et al, 2015), prompting questions about the potential health consequences of UPA in contaminated areas.…”
Section: Urban Food Productionmentioning
confidence: 99%
See 1 more Smart Citation